2014
DOI: 10.3945/jn.113.190264
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bovine Lactoferrin Alters Mucosal and Systemic Immune Cell Responses in Neonatal Piglets

Abstract: Lactoferrin (LF) is a multifunctional immune protein found at high concentrations in human milk. Herein, the effect of dietary bovine LF (bLF) on mucosal and systemic immune development was investigated. Colostrum-deprived piglets were fed formula containing 130 [control (Ctrl)], 367 (LF1), or 1300 (LF3) mg of bLF/(kg body weight · d). To provide passive immunity, sow serum was provided orally during the first 36 h of life. Blood, spleen, mesenteric lymph node (MLN), and ascending colon (Asc) contents were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 67 publications
1
42
0
Order By: Relevance
“…Furthermore, B. infantis has been shown to be immunomodulatory (17, 31) and bLf may promote the growth of B. infantis (16), suggesting the potential for synergistic effects. On the basis of our previous research (15, 19), by the seventh day of life bLf improved gastrointestinal development and immune system development compared with piglets fed formula alone. Thus, these early effects on the gastrointestinal and immune systems likely give the bLf-fed piglets an advantage over their formula-fed peers upon systemic challenge with S. aureus .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, B. infantis has been shown to be immunomodulatory (17, 31) and bLf may promote the growth of B. infantis (16), suggesting the potential for synergistic effects. On the basis of our previous research (15, 19), by the seventh day of life bLf improved gastrointestinal development and immune system development compared with piglets fed formula alone. Thus, these early effects on the gastrointestinal and immune systems likely give the bLf-fed piglets an advantage over their formula-fed peers upon systemic challenge with S. aureus .…”
Section: Discussionmentioning
confidence: 85%
“…One possible explanation for this could be that IFN-γ is an intracellular cytokine and its presence may be too low in the serum to detect. Previously, we found that spleen cells isolated from pigs fed bLf produced more IFN-γ and TNF-α than cells isolated from pigs fed a control diet (15). Although NK cells are the most likely potential sources of IFN-γ, it may be that peripheral memory T cells contain intracellular IFN-γ; both of these cells could release IFN-γ when needed during an immune response.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, industrial processes can significantly interfere with the bioavailability of the nitrogen content as well as the nutritional value of HPFs [12,13,21] . In addition, accumulating evidence has demonstrated the nutritional importance of the quality of the protein source for the postnatal maturation of the gastrointestinal tract in animal studies [19,22,23] .…”
Section: Introductionmentioning
confidence: 99%